Understanding about Takaful among students Nursing Part 4 Faculty of Health Science UiTM Puncak Alam / Muhammad Nabiljad Merikan. - Merikan, Muhammad Nabiljad (2019)
A study on Takaful understanding among students. The number of students involved is 50 sample from 500 (population). The method used is quantitative which is questionnaire through google and qualitative form which is library research as second method. The results show that Nursing students have a moderate level of understanding of Takaful on the objectives of the study. In conclusion, the emphasis of Takaful knowledge on students is important and should take seriously so that it can further boost the Takaful institution towards a higher than Conventional Insurance.